(3YGdejI JLGQI GdbQf GdMGOj h GdYTQjf (B(3) :s (3efXeI GdJLGQI GdYGdejI heDJeQGJgG GdhRGQjI (B((3hbGFY (B- (3eTGcd (B- (3JMOjGJ (B) /s - (3YHO GdYRjR, SejQ eMeOs ((3GdEScfOQjI(B: s (3GdecJH GdYQHj GdMOjK(B, s, 2006)
(3efXeI GdJLGQI GdYGdejI(B- (3GdLGJ (B1947- (3bhGYO GdEfXeGe Ch GdJaGhV defXeI GdJLGQI GdYGdejI(B- (3JShjI GdefGRYGJ aj EWGQ EJaGbjGJ efXeI GdJLGQI GdYGdejI ef SfZGahQI Gdi GdOhMI(B- (3GdeDJeQGJ GdhRGQjI defXeI GdJLGQI GdYGdejI(B- (3GdeDJeQ GdhRGQj GdQGHY HGdOhMI fhaeHQ (B2001- (3GdeDJeQ GdhRGQj GdNGeS CZSWS (B2003 - (3efXeI GdJLGQI GdYGdejI heDJeQGJgG GdhRGQjI ef GdefXhQ GdYQHjs
Keywords: (3eDJeQGJs; (3efXeI GdJLGQI GdYGdejIs